Women's experience of academic collaboration. - Carolyn M. Clark; Denise B. Watson (Adult Education Research Conference, 1997)
This study examines the experience of collaboration for women academics in adult education. While the women describe a range of collaborative experiences, they place the greatest value on more complex forms of collaboration in which the self, the partner(s), and the work exist in a highly dynamic and interactive relationship. This study suggests that collaboration provides one way in which women are creating life-giving spaces for themselves within the masculinist culture of the academy.